2021
DOI: 10.1016/j.ijcha.2021.100916
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid coronary revascularization versus percutaneous coronary intervention: A systematic review and meta-analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
3
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
0
4
3
5
Order By: Relevance
“…In this meta‐analysis, HCR and CABG had comparable rates of mortality and MACCE on both short‐ and long‐term follow up, findings that are in line with the results of previous meta‐analyses such as those by Hinojosa‐Gonzalez et al, Sardar et al, Zhu et al, and Reynolds et al 22,42–44 However, the durability of HCR was challenged with a significantly higher odds of repeat revascularization compared to CABG on long‐term follow‐up. This finding contrasts with a previous meta‐analysis by Sardar et al, 22 that reported similar rates of repeat revascularization between HCR and CABG groups and Van den Eynde et al 45 who reported a significantly lower rate of repeat revascularization in the HCR group compared to the CABG group. This difference could be explained by the relatively small sample size of the meta‐analysis by Sardar et al 22 and the fact that a fixed‐effect model meta‐analysis was conducted in both 45 .…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In this meta‐analysis, HCR and CABG had comparable rates of mortality and MACCE on both short‐ and long‐term follow up, findings that are in line with the results of previous meta‐analyses such as those by Hinojosa‐Gonzalez et al, Sardar et al, Zhu et al, and Reynolds et al 22,42–44 However, the durability of HCR was challenged with a significantly higher odds of repeat revascularization compared to CABG on long‐term follow‐up. This finding contrasts with a previous meta‐analysis by Sardar et al, 22 that reported similar rates of repeat revascularization between HCR and CABG groups and Van den Eynde et al 45 who reported a significantly lower rate of repeat revascularization in the HCR group compared to the CABG group. This difference could be explained by the relatively small sample size of the meta‐analysis by Sardar et al 22 and the fact that a fixed‐effect model meta‐analysis was conducted in both 45 .…”
Section: Discussioncontrasting
confidence: 92%
“…This finding contrasts with a previous meta-analysis by Sardar et al, 22 that reported similar rates of repeat revascularization between HCR and CABG groups and Van den Eynde et al 45 who reported a significantly lower rate of repeat revascularization in the HCR group compared to the CABG group. This difference could be explained by the relatively small sample size of the metaanalysis by Sardar et al 22 and the fact that a fixed-effect model meta-analysis was conducted in both.…”
Section: Sensitivity Analysis Including Only Rctscontrasting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, contrarily to the widespread belief, hybrid procedures with stents did not yield worse results over time in comparison with the nonhybrid group (likely owing to the evolution of drug‐eluting stents). We demonstrated in previous studies that patients treated surgically for coronary disease can be equally treated with LIMA to LAD plus saphenous vein grafts or stents for non‐LAD vessels with similar long‐term outcomes, 27–29 suggesting that contemporary stents can be as effective as other grafts to treat non‐LAD lesions. There is an interesting aspect in our study which we should highlight.…”
Section: Discussionmentioning
confidence: 80%